al-Qiyam al-Syakhshiyyah wa Tanfidzuha fi Ta’lim al-Lughah al-Arabiyyah - Muhammad Jafar Shodiq (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
The background of this research is the poor condition of young generations from the values of character and culture. School as an educational institution has the responsibility to establish and develop the character of students. This paper aims to determine the role of learning Arabic in character education, character education applications in learning the Arabic language and what the values can be internalized in the Arabic language learning. This study applied qualitative method using descriptive technique. The data were collected through observation, interviews, and documentation. The findings of study showed that : 1) The values of character education has been integrated by lecturers in teaching Arabic language include : religious, honest, tolerance, independent, democracy, curiosity, national spirit, communicative, love reading, respect, responsibility, discipline, environmental care, and recognize excellence. 2) How lecturer integrate character education values into Arabic learning include: adjust the lecture material, insert the value of character or try to take lessons in every lecture material, delivery value of the character through learning methods as well as trying to connect with the planting material and the implementation of the educational value of character in everyday life.